Anticoccidial effects of coumestans from Eclipta alba for sustainable control of Eimeria tenella parasitosis in poultry production - Michels, M. G.; Bertolini, L. C. T.; Esteves, A. F.; Moreira, P. [UNESP]; Franca, S. C. (Elsevier B.V., 2011)
The aim of this study was to evaluate the anticoccidial efficacy of a product containing coumestans from Eclipta alba. Experimental conditions were set up as to reproduce the environment conditions for husbandry adopted in commercial broiler farms. Broilers were raised in broiler chicken shed provided with feeders, drinkers, illumination and temperature control systems and floor covering to afford an adequate nourishing environment. Male Cobb broilers (240) were assigned to four experimental groups being each experimental group set apart in rice straw-covered shed isolated with wire mesh. One-day-old broilers were reared in a coccidian-free environment with ad libitum supply of filtered water and freely available standard feed, from the 1st to the 35th day of life. The T1 group received standard feed (negative control); T2 was treated with standard feed supplemented with 66 ppm of salinomycin (positive control); groups T3 and T4 had standard feed supplemented with the ethyl acetate fraction from methanolic extract of E. alba aerial parts, which contains the coumestans WL and DWL (120 and 180 ppm, respectively). The chicken broilers were individually infected with 2 x 104 oocysts of Eimeria tenella when they were 14 days old and were monitored weekly to evaluate zootechnical parameters such as weight gain and food conversion ratio. Counting of coccidial oocyst in chiken feces was assessed from random samples, from the 21st to 28th days of life, which corresponded to 7-14 days after the infection. Five chickens selected at random from each experimental group were subsequently euthanized at 21, 28 or 35 days of life to determine the lesion score in the cecal region and to excise a cecum portion for histopathological evaluation. The group treated with coumestans from E. alba presented an average weight gain and food conversion ratio higher than the negative control group and similar to the mean value of the positive control group. Coumestan-treated groups showed a significant decrease in the oocyst counting since the 21th day of life and displayed a reduced number of macroscopic lesions. Histopathological evaluations of cecum fragments showed that both treatments induced the migration of defense cells at the site of infection. A severe destruction of the cecal lining was found in the intestinal tract of broilers fed with a coumestans dose of 180 ppm. Overall, our results validate the use of a phytotherapy containing E. alba coumestans at a dose of 120 ppm as a therapeutic or prophylactic agent against avian coccidiosis. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Eclipta alba; Coumestans; Eimeriose; Anticoccidial; Avian coccidiosis